Civility: One or Many? Introducing "Argumentative Civility" - Hassan, Hareim Hadi (Informal Logic)

(untitled) (Informal Logic, 2025)
This project develops a novel framework of “argumentative civility” by analyzing political argumentation's nature and challenges. It distinguishes political disagreements from other domains, focusing on civility's dual role as both a facilitative and potentially oppressive tool. Key inquiries include: Who defines civility? Can it foster engagement without silencing dissent? The analysis integrates Western virtue argumentation theory with Islamic traditions of Munāẓara and Adab al-Jadal to build a cross-cultural model for civil discourse. Ultimately, this research aims to establish argumentative civility as a means of fostering peaceful coexistence and socio-political transformation through reasoned, inclusive debate across cultural boundaries.